Role of Video-Assisted Thoracoscopic Surgery in the Management of Pleural Empyema - Hossain, SM Shahadat; Jahan, Farhana Israt; Rahman, Md Shahinur; Majumdar, Md Neazul Islam; Islam, Khan Nazmul (Journal of Armed Forces Medical College, Bangladesh, 2022)
Background: Video-assisted thoracoscopic surgery (VATS) has revolutionized surgical management of patients with empyema. Thoracoscopic management of empyema includes VATS debridement and decortication. VATS debridement has been employed by many centres as the primary treatment option for early-stage empyema. Objective: To evaluate the outcome of VATS over open thoracotomy. Methods: This cross-sectional study was conducted in the department of Thoracic Surgery of Combined Military Hospital Dhaka from 01 January 2017 to 30 May 2018 among 30 patients (20 patients underwent VATS and 10 patients underwent open decortication/OD). The results were viewed with respect to baseline characteristics, preoperative management, operative and postoperative course. Results: Operative time and median in-hospital length of stay were shorter for the VATS group: 128 vs 140 minutes (p < .001), and 14 vs 11 days (p .03), respectively. The median postoperative length of stay was 12 days for the VATS group vs15 days for the OD group (p < .001). Complications after Video Assisted Thoracic Surgery is less like prolonged air leakage, infection and atelectasis. Conclusions: VATS decortications for empyema thoracis, complex effusion, haemothorax yields better results than open decortications. Patients treated with VATS have less postoperative complications. VATS debridement and decortication is safe and effective treatment in the management of empyema thoracis. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 19-22